2005
DOI: 10.1007/s10350-005-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Alvimopan, a Novel, Peripherally Acting, Mu Opioid Antagonist, for Postoperative Ileus After Major Abdominal Surgery

Abstract: In patients undergoing major abdominal surgery, alvimopan accelerated gastrointestinal recovery and time to the hospital discharge order written compared with placebo and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
203
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(216 citation statements)
references
References 50 publications
(24 reference statements)
6
203
3
1
Order By: Relevance
“…In study 14CL302, the lower incidence of vomiting in the alvimopan 12 mg group was statistically signifi cant compared to that in the placebo group. 54 A smaller proportion of patients in the alvimopan (6 and 12 mg) groups had serious adverse events that required prolonged hospitalization or readmission in comparison to those receiving placebo. 58 Discontinuations as a result of adverse events occurred to similar extents for alvimopan and placebo in the Phase 3 trials (Table 6), and of the few deaths reported, none was considered drug-related.…”
Section: Preclinical Studiesmentioning
confidence: 92%
See 3 more Smart Citations
“…In study 14CL302, the lower incidence of vomiting in the alvimopan 12 mg group was statistically signifi cant compared to that in the placebo group. 54 A smaller proportion of patients in the alvimopan (6 and 12 mg) groups had serious adverse events that required prolonged hospitalization or readmission in comparison to those receiving placebo. 58 Discontinuations as a result of adverse events occurred to similar extents for alvimopan and placebo in the Phase 3 trials (Table 6), and of the few deaths reported, none was considered drug-related.…”
Section: Preclinical Studiesmentioning
confidence: 92%
“…[53][54][55][56][57][58][59][60] The primary reason for surgery was rectal or colon cancer. 53,60 All were randomized, double-blind, placebo-controlled parallel studies comparing the effi cacy of alvimopan to that of placebo in hospitalized patients.…”
Section: Phase 3 Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators evaluated patients from the placebo arms of 3 phase III trials assessing the efficacy of an oral peripherally acting μ-opioid receptor antagonist for the management of POI. 5,13,16,51 Their findings represent an important source of postoperative recovery data from a controlled setting and a homogeneous patient population. The analysis of postoperative GI recovery and LOS patterns provides important insights into upper and lower GI recovery, symptoms, morbidity and mortality, LOS, and readmission after bowel resection (BR) in a large group of patients (n=383) receiving a standardized multimodal postoperative management protocol.…”
mentioning
confidence: 94%